Village Government's Role in Advancing Agricultural Development Through Supportive Policies - Apriana, Dwi; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
Background: Indonesia, a tropical country with rich agricultural potential, faces challenges in optimizing its agricultural sector. Specific Background: Despite significant contributions to the economy and employment, issues like low human resource capacity and dependency on food imports hinder productivity. Knowledge Gap: The role of village governments in facilitating agricultural development, particularly in rural areas like Grabagan Village, remains underexplored. Aims: This study analyzes the village government's role in agricultural development in Grabagan Village, focusing on key success indicators. Results: Findings indicate that the village government functions effectively as a facilitator, mobilizer, and regulator, yet faces challenges in resource mobilization and farmer engagement. Novelty: This research enhances understanding of local governance's influence on agricultural outcomes. Implications: The study highlights the need for improved collaboration between the village government and farmers to optimize resource allocation and align agricultural initiatives with local needs for sustainable development. Highlights: The village government serves as a crucial facilitator in agricultural initiatives, providing necessary infrastructure and budget support. Effective mobilization of resources and farmer involvement in planning processes are essential for enhancing agricultural productivity. Addressing challenges in local governance can significantly improve sustainable agricultural development in rural areas. Keywords: Village Government, Agricultural, Farmer Empowerment, Facilitation, Mobilization